Rice production worldwide - Chauhan, Bhagirath Singh; Jabran, Khawar; Mahajan, Gulshan (Springer, 2017)
This book addresses aspects of rice production in rice-growing areas of the world including origin, history, role in global food security, cropping systems, management practices, production systems, cultivars, as well as fertilizer and pest management. As one of the three most important grain crops that helps to fulfill food needs all across the globe, rice plays a key role in the current and future food security of the world. Currently, no book covers all aspects of rice production in the rice-growing areas of world. This book fills that gap by highlighting the diverse production and management practices as well as the various rice genotypes in the salient, rice-producing areas in Asia, Europe, Africa, the Americas, and Australia. Further, this text highlights harvesting, threshing, processing, yields and rice products and future research needs. Supplemented with illustrations and tables, this text is essential for students taking courses in agronomy and production systems as well as for agricultural advisers, county agents, extension specialists, and professionals throughout the industry.- Resumé vydavatel
Includes index.
Keywords: rýže; zemědělský trh; rice; agricultural market; elektronické knihy; sborníky; electronic books; papers of several authors